3(5-x)=11+2x

Simple and best practice solution for 3(5-x)=11+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5-x)=11+2x equation:



3(5-x)=11+2x
We move all terms to the left:
3(5-x)-(11+2x)=0
We add all the numbers together, and all the variables
3(-1x+5)-(2x+11)=0
We multiply parentheses
-3x-(2x+11)+15=0
We get rid of parentheses
-3x-2x-11+15=0
We add all the numbers together, and all the variables
-5x+4=0
We move all terms containing x to the left, all other terms to the right
-5x=-4
x=-4/-5
x=4/5

See similar equations:

| (2x-7)^2+3(7-2x)-180=0 | | x*5+42=2*x | | 19h-8=-8+h+18h | | z+96=912 | | f/18=26 | | 3d+16=-20-6d | | 8+12x=40 | | 4*(x-1)-3*(x+3)=3*x+5 | | 3x2-28x+9=0 | | -7b-2=4-9b | | -2x2+20x-46=0 | | 21v=168 | | .6667x-6=18 | | 30=t/25 | | 10+5g=-g-8 | | 30=t25 | | -9-y=-4y+9 | | 17=t−42 | | 7x+40=-2 | | 7x2-6x+2=0 | | b+38=61 | | -6+2g=7g+9 | | -2m-3=-10-9m | | 7x2-22x+3=0 | | r+6=6+r | | 7x2-35=0 | | 0.5x+3=-9 | | 5(3x+9)-2x=15x-2(x-5)+10 | | -4c+9=9-4c | | -10-6h=-10-5h | | 10-8z=-8z+10 | | -4(2x-8)=5+7(-2x+7) |

Equations solver categories